2018
DOI: 10.1002/jcb.27483
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal decoction of Wenshen Yangxue formula improved fertility and pregnancy rate in mice through PI3K/Akt signaling

Abstract: Objective: Traditional Chinese medicine (TCM) is an effective management to infertility. The association between TCM-mediated fertility and inhibition of phosphatidylinositol-3-kinase (PI3K) would be investigated.Methods: Institute of Cancer Research mice were treated with three herbal decoctions, named Wenshen Yangxue formula, Wenshen formula, and Yangxue formula, plus with human gonadotropins. PI3K inhibitor wortmannin was administrated to half of mice. Some index such as body weight, fertility ability would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several reports have suggested that traditional herbal formulas and medicinal herbs successfully improve endometrial receptivity and might be an alternative option for improving the outcome of embryo implantation [192][193][194]. Many herbal formulas have been studied for enhancing the embryo implantation rate in animal studies and clinical study [195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213]. Among these formulas, Erbu Zhuyu decoction and Tokishakuyakusan (TJ-23, Danggui Shaoyao san in Chinese) have been reported to induce autophagy via the expression of Beclin1 and LC3 [208,214,215].…”
Section: Possible Role Of Autophagy On the Effect Of Medicinal Herbal Drugs As Embryo Implantation Enhancermentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have suggested that traditional herbal formulas and medicinal herbs successfully improve endometrial receptivity and might be an alternative option for improving the outcome of embryo implantation [192][193][194]. Many herbal formulas have been studied for enhancing the embryo implantation rate in animal studies and clinical study [195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213]. Among these formulas, Erbu Zhuyu decoction and Tokishakuyakusan (TJ-23, Danggui Shaoyao san in Chinese) have been reported to induce autophagy via the expression of Beclin1 and LC3 [208,214,215].…”
Section: Possible Role Of Autophagy On the Effect Of Medicinal Herbal Drugs As Embryo Implantation Enhancermentioning
confidence: 99%
“…BaelanChagsangBang -- [236] Bangdeyun and its component DS147 -- [196,197] Buganshen recipe -- [198] BuShenAnTai recipe -- [201] Bushen Tiaoxue Granules and Kunling Wan -- [202] Dingkun Pill -- [206,207,212] Erbu Zhuyu decoction -Increases the Beclin1 and LC3B [204,208] Gushen'antai pills -- [195] Liuwei Dihuang Granule -- [199] Shoutaiwai recipe -- [200] Tokishakuyakusan(Danggui Shaoyao san) -Induces autophagy and mitophagy via increasing PINK1 and LC3 but reducing p62 [203,214,215] Wenshen Yangxue decoction -- [205,211] Xianziyizhen Recipe -- [237] Yeosin-san Paeonia lactiflora and Cyperus rotundus - [213,238] Yiqixue buganshen recipe -- [198] Zhuyun recipe -- [210] Angelica gigas Decusirol Block autophagic flux by suppressing cathepsin C expression [216,221] Cnidium officinale -- [239] Cyperus rotundus -Increases LC3B II/LC3B and Beclin1 [223,229] Paeonia lactiflora Paeoniflorin Induces autophagy via inhibition of AKT/mTOR [114,225,230] Panax quiquefolius (American Ginseng) Ginsenoside Rb1 and Rg1…”
Section: Name Active Components Role In Autophagy Referencesmentioning
confidence: 99%
“…It is one of the earliest and most widely used dosage forms in Chinese medical practice and has existed for thousands of years [4]. Not only is decoction a relatively fast and cheap process that is readily available to patients, but also the flexible prescription can satisfy the needs of TCM treatment according to syndrome differentiation [5], Nevertheless, how effective the drug prescription is, depends on the quality of decoction [6]. Furthermore, decoction of TCM is a complex system consisting of many components.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 A number of studies have revealed that traditional Chinese medicine (TCM) has an important role in the enhancement of the parameters of spermatozoa, including sperm count, viability, motility, and morphology. [20][21][22] Not only can it treat male infertility but it also improves the symptoms of other diseases, such as premature ejaculation, 23 erectile dysfunction. 24 In terms of sperm quality, studies show that the total sperm motility of patients who had received TCM combined with vitamins for twelve weeks is better than those who only received vitamins.…”
mentioning
confidence: 99%